PENGARUH VARIASI PENAMBAHAN PATI BIJI DURIAN (Durio zibethinus Murr.) DAN PATI JAGUNG TERHADAP KARAKTERISTIK EDIBLE FILM: The Effect of Additional Variations of Durian Seed Starch (Durio zibethinus Murr.) and Corn Starch on the Characteristics of Edible Film - Widayanti Karolina, Rosiana Ulfa, Bagus Setyawan (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2022)
Technological advances in the industrial sector in recent years will be followed by the increasing use of plastics as packaging materials. Therefore, an alternative solution is the use of biodegradable packaging such as edible film. In this study, the basic ingredients of durian seed starch and corn starch were combined. The research design used was a completely randomized design (CRD) with 6 treatments where each treatment was repeated four times with a combined ratio of PBD: PJ, namely 3.5g: 1.5g, 3g: 2g, 2.5g: 2.5g, 2g: 3g and 1.5g: 3.5g. The edible film obtained was then tested for thickness, water vapor transmission rate, moisture content, and solubility tests. Based on research and discussion concluded that the manufacture of edible films with a combination of durian seed starch and corn starch on the thickness parameter in the EF1 treatment with a value of 0.03 mm. The water vapor transmission rate is 6.875 g/m2/24 hours. The water content parameter is found in the EF1 treatment (3.5g: 1.5g) which is 14.75%. The best solubility of the edible film was in the sample EF2 (3g: 2g) which was 76.5%. The use of durian seed starch and corn starch as the basic ingredients for making edible films has considerable potential.